2017
DOI: 10.1002/aur.1899
|View full text |Cite
|
Sign up to set email alerts
|

Sleep patterns predictive of daytime challenging behavior in individuals with low‐functioning autism

Abstract: We analyzed over 20,000 nights of sleep from 67 individuals with autism to investigate whether daytime behaviors can be predicted from prior sleep patterns. Better-than-chance accuracy was obtained for 81% of individuals, with measures of night-to-night variation in sleep timing and duration most relevant for accurate prediction. Our results highlight the importance of regular sleep patterns for better daytime functioning and represent a step toward the development of 'smart sleep technologies' to pre-empt beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 48 publications
7
46
0
Order By: Relevance
“…Alterations in specific sleep stages may also be associated with different ASD phenotypes; prolonged REM latency has been associated with regression (97). Other maladaptive behaviors, such as self-injury, tantrums and aggression, are associated with shorter sleep durations in ASD (15), and children with ASD with poorer sleep quality also have higher rates of internalizing and externalizing behavioral disorders and lower levels of adaptive functioning (98, 99).…”
Section: Meta-synthesis Of Theories Underlying Common Medical Comorbimentioning
confidence: 99%
“…Alterations in specific sleep stages may also be associated with different ASD phenotypes; prolonged REM latency has been associated with regression (97). Other maladaptive behaviors, such as self-injury, tantrums and aggression, are associated with shorter sleep durations in ASD (15), and children with ASD with poorer sleep quality also have higher rates of internalizing and externalizing behavioral disorders and lower levels of adaptive functioning (98, 99).…”
Section: Meta-synthesis Of Theories Underlying Common Medical Comorbimentioning
confidence: 99%
“…58 Sleep problems are not only linked to core symptoms of autism, but also with associated symptoms such as internalizing and externalizing behaviour problems and anxiety. 56 Nonetheless, these associations are not consistently confirmed in the literature, 59 leaving open the possibility that poorer sleep observed in children with ASD with a more severe symptomatology would be a mere reflection of brain immaturity, challenging a sleep-behaviour relationship. Indeed, brain maturation leads not only to behavioural changes and improvements in cognitive skills, but also shapes sleep features.…”
Section: Sleep-related Clinical Characteristics Associated With Autismmentioning
confidence: 99%
“…[77][78][79] Second, sleep quality seems to be temporally bound to subsequent daytime behaviour. Using an extensive longitudinal data set, Cohen et al 59 investigated whether prior sleep quantity and quality in children predicted subsequent daytime behaviour, and whether cumulative sleep loss over several nights increased the risk of behavioural problems the following day. Results confirmed a predictive relationship between sleep on the previous night and the presence of challenging behaviours the next day.…”
Section: Is There a Directionality In The Relationship Between Sleep mentioning
confidence: 99%
“…Numerous studies have shown that a wide variety of persistent sleep difficulties experienced by ASD children exacerbate their core autistic symptoms (25) and are associated with many conditions that co-occur with ASD including increased anxiety, sensory over-responsivity (26), selfstimulatory behavior, and daytime challenging behavior (27), as well as medical comorbidities such as gastrointestinal problems (12) and epilepsy (28). Among children with ASD, poor sleepers exhibit more ritualistic, compulsive, irritable, and hyperactive behavior than good sleepers (29,30).…”
Section: Introductionmentioning
confidence: 99%